How Place Matters: A View from the Sunbelt. (January 2017) - Strom, Elizabeth
Place Matters speaks eloquently of the shifts within and between US metropolitan areas, and the problems of growing racial and economic segregation. It's argument is more compelling, however, in describing the "legacy" cities of the Northeast and Midwest than it is in illuminating the most pressing issues for Sunbelt cities. Sunbelt metropolitan areas continue to grow, but they exhibit different economic geographies and political dynamics. This article probes some of these differences and suggests future avenues for research.